Analog Rice Production Training at the Sakinah Family Farmer Group (KWT) in Kulon Progo: Pelatihan Produksi Beras Analog Pada KWT Keluarga Sakinah Kulon Progo - Ichlasia Ainul Fitri; Chatarina Lilis Suryani; Bayu Kanetro; Dadang Mulyana; Ayu Pratiwi Nurhidayati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This community service activity was a collaboration between CSR Pertamina Parta Niaga Fuel Rewulu and Deparrtment of Food Technology, Faculty of Agroindustry, Universitas Mercu Buana Yogyakarta which conducted in the form of a training program on analog rice production for the Women Farmer Group (KWT)